THE RELATIONSHIP BETWEEN CHARACTERISTICS AND KNOWLEDGE OF POSTPARTUM MOTHERS REGARDING POSTPARTUM DANGER SIGNS IN THE JUWANA HEALTH CENTER AREA PATI - Widyastuti, Erna (Postgraduate Program , Poltekkes Kemenkes Semarang, 2025)
Background: The postpartum period is the period immediately after giving birth until the physiology of the reproductive organs recovers to their pre-pregnancy state which lasts for 6-8 weeks. The purpose of this study was to determine the relationship between age, education, and occupation characteristics with postpartum mothers' knowledge of postpartum danger signs in the Juwana Health Center Area, Pati Regency. Methods: This study used a quantitative method with correlation analysis, and total sampling and the sample was 51 respondents.Results: The study results showed that the majority of respondents had good knowledge about postpartum danger signs as many as 29 respondents (56.9%) while those with less knowledge were 22 respondents (43.1%). The results of the chi-square test analysis at (α = 0.05) showed that the relationship between age characteristics and knowledge of postpartum danger signs p value = 0.001, education characteristics with knowledge of postpartum danger signs p value = 0.000, job characteristics with knowledge of postpartum danger signs p value = 0.00 so that there is a relationship between age characteristics, education and jobs with postpartum mothers' knowledge of postpartum danger signs in the Juwana Health Center Area, Pati Regency. Conclusion: There is a relationship between age, education and jobs with postpartum mothers' knowledge of postpartum danger signs in Juwana Health Center Area, Pati Regency.This study can be information and increase knowledge for mothers about danger signs that can occur during the postpartum period and can detect if danger signs occur.